At the Crossroads between Violence and Migration: Migrant Women's Grassroots Struggles Against Intersectional Violence in Spain - Gaudioso, Desirè (PARTECIPAZIONE E CONFLITTO, 2025)
This article examines the intersectional violence experienced by migrant women in Spain, emphasizing the complexity of their experiences beyond traditional conceptions of gender-based violence (GBV). It critiques the limited scope of existing research on violence against migrant women and calls for an intersectional approach that accounts for how race, class, sexuality, and other axes of oppression intersect with gender, shaping both experiences of violence and strategies of resistance. The study focuses on how migrant women resist violence by collectively developing their own discourse on the issue within migrant women's groups. Through discourse analysis, it explores the centrality of violence in these groups' narratives and highlights their alternative, critical, and intersectional perspectives on the topic. Lastly, it challenges essentialist narratives on violence against migrant women, highlighting their agency in resisting and shaping their own perspectives on the issue.